Verbesina encelioides: cytotoxicity, cell cycle arrest, and oxidative DNA damage in human liver cancer (HepG2) cell line - Al-Oqail, Mai M. (BMC Complement Altern Med, 2016)
BACKGROUND: Cancer is a major health problem and exploiting natural products have been one of the most successful methods to combat this disease. Verbesina encelioides is a notorious weed with various pharmacological properties. The aim of the present investigation was to screen the anticancer potential of V. encelioides extract against human lung cancer (A-549), breast cancer (MCF-7), and liver cancer (HepG2) cell lines. METHODS: A-549, MCF-7, and HepG2 cells were exposed to various concentrations of (10–1000 μg/ml) of V. encelioides for 24 h. Further, cytotoxic concentrations (250, 500, and 1000 μg/ml) of V. encelioides induced oxidative stress (GSH and LPO), reactive oxygen species (ROS) generation, mitochondrial membrane potential (MMP), cell cycle arrest, and DNA damage in HepG2 cells were studied. RESULTS: The exposure of cells to 10–1000 μg/ml of extract for 24 h, revealed the concentrations 250–1000 μg/ml was cytotoxic against MCF-7 and HepG2 cells, but not against A-549 cells. Moreover, the extract showed higher decrease in the cell viability against HepG2 cells than MCF-7 cells. Therefore, HepG2 cells were selected for further studies viz. oxidative stress (GSH and LPO), reactive oxygen species (ROS) generation, mitochondrial membrane potential (MMP), cell cycle arrest, and DNA damage. The results revealed differential anticancer activity of V. encelioides against A-549, MCF-7 and HepG2 cells. A significant induction of oxidative stress, ROS generation, and MMP levels was observed in HepG2 cells. The cell cycle analysis and comet assay showed that V. encelioides significantly induced G2/M arrests and DNA damage. CONCLUSION: These results indicate that V. encelioides possess substantial cytotoxic potential and may warrant further investigation to develop potential anticancer agent. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12906-016-1106-0) contains supplementary material, which is available to authorized users.